2010
DOI: 10.1002/bdrb.20235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginkgo biloba extract on the embryo‐fetal development in Wistar rats

Abstract: The GBE treatment in pregnant Wistar rats, during the tubal transit and implantation period, caused no toxic effect on the maternal organism and did not induce embryonic death, growth retardation, and/or fetal malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
(64 reference statements)
1
9
1
Order By: Relevance
“…This incidence before laparatomy not only suggests abortion, but also fetotoxicity (Yakubu et al, ). The present results are compatible with the published data that concluded that Ginkgo has no teratogenic effects (Pinto et al, ; Fernandes et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This incidence before laparatomy not only suggests abortion, but also fetotoxicity (Yakubu et al, ). The present results are compatible with the published data that concluded that Ginkgo has no teratogenic effects (Pinto et al, ; Fernandes et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, the dose 14.8 mg/kg bw/day of Ginkgo was maternally toxic including decreased maternal body weights, organ weight alterations, and vaginal bleeding. These results are inconsistent with the data indicated that Ginkgo had no systemic maternal toxicity in rats (Pinto et al, ; Fernandes et al, ). This discordance might be related to the selective effect on integrity of maternal homeostasis (Almeida and Lemonica, ), the extract may not be better tolerated by the animals at high dose (Yakubu et al, ), or to different dose and animal.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The novelty of this study is the investigation of effects of Ginkgo biloba extract on pup brains of hyperhomocysteinemic mothers. Although there are some studies that report findings in rats exposed to EGb prenatally (Li et al , ; Fernandes et al , ), administration of EGb together with methionine to either pregnant or non‐pregnant rats has not been reported previously. It was found that EGb partially, but significantly, antagonized some effects of homocysteine on pup brain.…”
Section: Discussionmentioning
confidence: 97%
“…Direct comparison of these studies may be confusing since study designs are somewhat dissimilar. Since some effects of EGb are dose dependent (Li et al , ; Fernandes et al , ), when considering its effect on cognition this fact should also be taken in to account. Shif et al () reported that EGb does not improve working and reference memory, but it can promote the learning of spatial information in rats.…”
Section: Discussionmentioning
confidence: 99%